Exploring the Impact of Qur’anic Recitation Intensity on the Spiritual Intelligence of Female Islamic Boarding School Students - Fiani, Tuti; Jasiah , J; Ramdhani , Muhammad Tri; Syarif , Ahmad; Khoerunnisa , Nazila (Universitas Muhammadiyah Surakarta, 2025)
This study was motivated by the low manifestation of spiritual intelligence among santriwati at Al-Wafa Putri Islamic Boarding School in Palangka Raya, despite the implementation of Quran reading and memorization programs. The aim of the research is to determine the effect of Quran reading intensity on students’ spiritual intelligence. Using a quantitative method with a correlational approach, hypothesis testing showed a significance value of p = 0.000, indicating a strong positive relationship between Quran reading intensity and spiritual intelligence. Based on simple regression analysis, it was found that 36.4% of the variance in spiritual intelligence is influenced by the intensity of Quran reading, while the remaining 63.6% is affected by other uncontrolled factors. These findings highlight that regular and consistent engagement with the Quran significantly enhances spiritual intelligence. The habit of reading the Quran not only strengthens religious practices but also contributes to character building and inner spiritual growth. This suggests the need for Islamic boarding schools to implement meaningful, consistent, and integrated Quran recitation programs as part of their daily student development activities. The research emphasizes that spiritual intelligence can be nurtured through structured and ongoing religious activities, especially through reading and internalizing the Quran.